Anti-HIV activity of ellagitannins from alder tree fruits - Trokhymchuk, T.Yu.; Shalamay, A.S.; Zavelevich, M.P.; Palchykovska, L.G.; Vasylchenko, O.V.; Rybalko, S.L.; Starosyla, D.B.; Diadiun, S.T. (Вiopolymers and Cell, 2018)
Aim. To assess the inhibitory activity of ellagitannin complex of the purified extract from the fruits of white alder and black alder in non-eukaryotic polymerase systems and to analyze the effects of these substances on the reverse transcriptase of murine leukemia virus and HIV in vitro. Methods. Chronically infected MT4/BIII culture of human leukemic cells was used as the HIV source. Anti-HIV activity of the ellagitannin-containing extract was estimated by the reduction of HIV infectious titer in the MT-4 cells. The inhibitory effects of the extract on retroviral reverse transcriptase, T7 RNA-polymerase and Taq polymerase were also studied in cell-free systems. Results. The ellagitannin extract inhibited activities of the reverse transcriptase of murine leukemia retrovirus, T7 RNA-polymerase, and Taq polymerase. It also reduced the HIV infectious titer in MT-4 cells with IC 50 of 1.5 μg/ml and selectivity index of 87. Conclusions. The ellagitannin complex possesses a significant anti-HIV activity. Its in vitro antiviral effect is achieved with a relatively low toxicity Мета. Оцінити інгібувальну активність комплексу елаготанінів в очищеному екстракті плодів вільхи сірої і вільхи клейкої у відношенні полімераз, що не є полімеразами еукаріот, з метою скринінгу та проаналізувати вплив досліджуваних речовин на зворотну транскриптазу вірусу мишачої лейкемії та на репродукцію ВІЛ in vitro. Методи. Джерелом ВІЛ була хронічно інфікована культура клітин лейкемії людини МТ4/ВІІІ. Анти-ВІЛ активність комплексу елаготанінів визначали за зниженням інфекційного титру ВІЛ після зараження вірусом клітин МТ-4. Визначали інгібуючий ефект елаготанінів на активність ретровірусної зворотної транскриптази, РНК-полімерази фага Т7 і Taq-полімерази в безклітинних системах Результати. Досліджуваний екстракт елаготанінів виявився ефективним інгібітором активності зворотної транскриптази вірусу мишачої лейкемії, РНК-полімерази фага Т7 і Taq-полімерази. Комплекс елаготанінів ефективно знижував інфекційний титр ВІЛ для клітин МТ-4. IC50 становила 1,5 мкг/мл, а індекс селективності дорівнював 87. Висновки. Досліджуваний комплекс елаготанінів виявляє виражену анти-ВІЛ активність. Противірусний ефект in vitro досягався при відносно низькій токсичності. Цель. Изучить ингибирующую активность комплекса эллаготаннинов в очищенном экстракте соплодий ольхи серой и ольхи клейкой в отношении полимераз, не являющихся полимеразами эукариот, и проанализировать влияние этих веществ на активность обратной транскриптазы вируса мышиного лейкоза и на репродукцию ВИЧ in vitro. Методы. Источником ВИЧ служила хронически инфицированная культура клеток лейкоза человека МТ4/ВІІІ. Анти-ВИЧ активность комплекса эллаготаннинов определяли по снижению инфекционного титра ВИЧ после заражения вирусом клеток МТ-4. Определяли ингибирующий эффект эллаготаннинов на активность ретровирусной обратной транскриптазы, РНК-полимеразы фага Т7 и Taq-полимеразы. Результаты. Исследуемые эллаготаннины оказались эффективными ингибиторами активности обратной транскриптазы вируса мышиного лейкоза, РНК-полимеразы фага Т7 и Taq-полимеразы. Исследуемый комплекс эллаготаннинов эффективно снижал инфекционный титр ВИЧ для клеток МТ-4. IC50 составляла 1,5 мкг/мл при индексе селективности 87. Выводы. Изученный комплекс эллаготаннинов обладал выраженной анти-ВИЧ активностью. Противовирусный эффект in vitro достигался при относительно низкой токсичности.